DESCRIPTION AND PRESENTATION OF THE ALLERGIC CONJUNCTIVITIS CASUISTIC - Carmen Tiutiuca; Dragos Cristian Voicu; Lucian Indrei; Ana Magdalena Bratu; Aurelia Caraiane; Constantin Iulian (Romanian Journal of Oral Rehabilitation, 2023)
Allergic conjunctivitis is a common eye condition characterized by inflammation of the conjunctiva, which is the thin membrane that covers the inside of the eyelids and the exposed part of the eyeball. Allergies are the main cause of allergic conjunctivitis, and substances called allergens trigger an inflammatory reaction in the conjunctiva. The causes of allergic conjunctivitis are related to the reaction of the immune system to specific allergens. When a person with an allergic sensitivity comes in contact with an allergen, the immune system releases histamines and other chemicals that cause inflammation and irritation of the conjunctiva. Seasonal allergic conjunctivitis occurs in certain seasons of the year, being mainly caused by plant pollen. Symptoms include redness, swelling, itching, excessive tearing, and watery or mucous secretion. Treatment involves avoiding allergens and using antiallergic eye drops. Perennial allergic conjunctivitis is a chronic form that can occur as much as possible and is caused by persistent allergens such as dust mites, mold, or animal hair. Symptoms and treatment are similar to those of seasonal allergic conjunctivitis but often involve a longer and more complex approach.